The art of going green: an analysis of the determinants of organizational citizenship behavior towards the environment and environmental performance - Satriawan, Budhie; Satyawisudarini, Inne; Johan, Ahmad (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
Sensitivity to environmental issues today has prompted organizations to motivate their members to participate in implementing environmentally sound practices. This study was conducted with the aim of examining the influence of intrinsic motivation and organizational culture on organizational citizenship behavior towards the environment (OCBE) and its impact on the environmental performance of employees in manufacturing companies in Bandung, West Java. This study also examines the mediating role of OCBE on the influence of intrinsic motivation and organizational culture on environmental performance. Respondents in the study were selected using purposive sampling technique. The data of this study was collected by survey method by distributing questionnaires to respondents which was measured using a 5-point Likert scale. The findings of this study indicate a positive influence of intrinsic motivation and organizational culture on OCBE and environmental performance, and prove that OCBE can affect environmental performance. This study also emphasizes the mediating role of OCBE on the influence of intrinsic motivation and organizational culture on the environmental performance of employees in manufacturing companies in Bandung, West Java. This study highlights the determinants of OCBE and environmental performance from contextual (organizational culture) and personal (intrinsic motivation) factors.